Aktivitas Perawatan Sistem Bahan Bakar Mesin Diesel Tipe 12 PC4 – 2V - Wibowo, Waris; Astriawati, Ningrum; Kristianto, Lukas; Baskoro, Romi (Politeknik Bumi Akpelni, 2024)
Fuel system maintenance is one system that plays an important role in the smooth operation of a diesel engine, because each diesel engine will not be separated from fuel for the combustion process in running or operating an engine. The purpose of this study is to find out how the maintenance activities of the diesel engine fuel system type 12 PC4 – 2V on KM ships. Mutiara Berkah II which is one of the cruise fleets owned by PT. Atosim Lampung Sailing. The research methodology used is qualitative descriptive with field research. Data collection was used using interview techniques, observation and documentation. The results showed that diesel engine fuel system maintenance activities as the main mover on KM ships. Mutiara Berkah II at PT. Atosim Lampung The cruise has been going well.